Pengembangan Media Pembelajaran Matakuliah Sistem Operasi Jaringan Berbasis Smartphone - Martanto Martanto; Cep Lukman Rohmat (LPPM UBHINUS MALANG, 2021)
Students who registered at STMIK IKMI Cirebon in the last 3 years showed that 51% of applicants were from SMK graduates. Even though he comes from a vocational school, it is still very difficult to understand how to start learning about network operating systems. This is evident from the results of the Network Operating System lectures where only 1-2 people pass in each class. The use of smartphone media is expected to make it easier for lecturers to convey learning material so that the pattern of student center learning activities can run better without knowing time which means that students as learning objects will be able to better understand the material well. This study uses the Analysis, Design, Development, Implementation and Evaluation (ADDIE) development model. This research is divided into 5 stages, namely: the first stage the researcher conducts the analysis, there are two stages of analysis, namely performance analysis and needs analysis, the second stage the researcher makes a system design design which includes learning objectives, assessment instruments, exercises, content, subject matter analysis, lesson planning and media selection, the third stage the researchers began to create a system which includes the activities of making, buying, and modifying teaching materials to achieve the goals of the learning that have been determined, the fourth stage the researcher applies the system that has been created, the data generated in the application will be used for further improvement processes, In the fifth stage, the researcher evaluates the data that can be obtained at the previous stage, whether or not improvements are needed in the system that has been made. The results of the User Acceptance Test (UAT) in this study indicate that the learning media for the smartphone-based network operating system course is quite good because it has a percentage value that is above 70% on average.